An image-based narrative intervention to manage interview anxiety and performance. Issue 1 (20th July 2020) - Lin-Stephens, Serene
Abstract: A visual narrative intervention – Serious Storytelling with Images – was proposed to manage interview anxiety and performance. Its ability to evocate significant incidents and enhance narratives construction was evaluated ideographically in two case studies. The findings suggest varying levels of sophistication in interviewee actions, challenges encountered, and perceived roles of images. Counselors can refer to the hierarchical concepts when tailoring interview training and coaching. Further investigation is highly recommended to confirm and measure intervention effects.